Spatiotemporal changes of local hemodynamics and plaque components during atherosclerotic progression in rabbit. (June 2022) - Li, Xiaoyin; Liu, Xiao; Liang, Ye; Deng, Xiaoyan; Fan, Yubo
Highlights: The blood flow and LDL transport were numerically simulated in the rabbit aorta. The histological and immunohistochemical staining were experimentally evaluated. The HEs became better firstly, then got slightly worse and lastly improved again. The local hemodynamics and plaque components vary nonlinearly. A methodology was established for understanding of the atherosclerosis mechanisms. Abstract: Background and objective: Recent evidence demonstrates that the atherogenic process is discontinuous. Our goal is to study changes of plaque components and local hemodynamics during atherosclerotic progression. Methods: The histological and immunohistochemical staining of high-fat diet rabbit aorta were evaluated at 0, 8, 10 and 12 weeks, respectively. In addition, the blood flow and LDL transport were simulated at the above four time points. Results: The plaque thickness at different characteristic regions increased at different rates. The collagen continued to increase, while the elastin, fibronectin, macrophages and smooth muscle cells increased first and then decreased. The relative surface LDL concentration decreased at 8 weeks, and then it increased first and decreased slightly. Meanwhile, the hemodynamic environment became better firstly at 8 weeks, then got slightly worse and lastly improved again. Conclusions: The local hemodynamics and plaque components vary nonlinearly during atherosclerotic progression in rabbit aorta.